2016
DOI: 10.1007/s10266-016-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Stain susceptibility of composite and ceramic CAD/CAM blocks versus direct resin composites with different resinous matrices

Abstract: To evaluate the stain susceptibility of CAD/ CAM blocks and direct composite after long term exposure to various staining agents. 40 disk-shaped samples were fabricated from each of nine materials; six CAD/CAM (Vitablocs Mark II, Paradigm MZ100, Experimental Vita Hybrid Ceramic, Vita Enamic, Experimental Kerr and Lava Ultimate) and three direct composites (Filtek Supreme, Venus Diamond and Filtek Silorane). Samples were randomly divided into five groups (n = 8) according to different staining solutions (distil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 34 publications
10
91
1
4
Order By: Relevance
“…The study by Alharbi et al, on the color stability of feldspathic ceramic blocks, hybrid ceramic blocks, composite blocks, and direct composites, reports that the highest discoloration occurred in wine and coffee exposure. Also, the ceramic and composite CAD/CAM blocks have a lower staining susceptibility than methacrylate‐based direct composite …”
Section: Discussionmentioning
confidence: 99%
“…The study by Alharbi et al, on the color stability of feldspathic ceramic blocks, hybrid ceramic blocks, composite blocks, and direct composites, reports that the highest discoloration occurred in wine and coffee exposure. Also, the ceramic and composite CAD/CAM blocks have a lower staining susceptibility than methacrylate‐based direct composite …”
Section: Discussionmentioning
confidence: 99%
“…Both materials have similar filler particles and aggregated zirconia-silica cluster filler, but the structure of resin monomers and filler loadings were different. In some studies, it has been shown that FU (or Filtek Supreme) was most prone to discoloration (16,17), which might be attributed to its less-than-ideal integration of the nano-aggregated cluster fillers that are loosely bound agglomerates of nano-sized particles. Nano-composites and their clusters have a much larger surface area per unit mass, which may cause staining when their interface is not perfectly silanized and integrated into the resin (18).…”
Section: Discussionmentioning
confidence: 99%
“…Stained samples from a previous investigation were used in this study. Their preparation and staining are described in detail by Alharbi et al In brief, 40 disk‐shaped samples measuring 10 mm in diameter and 1 mm in thickness were constructed from each material (Table ) . The CAD/CAM blocks were sectioned using a low‐speed diamond saw (Minitom; Struers, Ballerup, Denmark) under water cooling.…”
Section: Methodsmentioning
confidence: 99%
“…This study was carried out as part of a series of studies on resin‐based CAD/CAM materials. The first part aimed to evaluate the stain susceptibility of resin‐based CAD/CAM materials compared to direct resin composites with various resinous matrices . The subsequent part was designed to evaluate the efficacy of bleaching on stain removal.…”
Section: Introductionmentioning
confidence: 99%